Asymptotic Behaviour of Discrete Fractional Keynesian Cross Models - Dhawan, Sangeeta; Jonnalagadda, Jagan Mohan (Journal of Applied Nonlinear Dynamics, 2026)
This article considers a fractional analogue of the discrete Keynesian cross model. We propose the corresponding fractional difference equation, which describes the dynamics of national income, and obtain its solution in terms of the discrete Mittag--Leffler function. Further, we discuss the asymptotic behavior of national income described by this solution and offer two numerical examples to show the applicability of established results.